The Incidence of Three Roots and Four Root Canals in Endodontically Treated Mandibular First Molars in Iraqi Population (Mustansiria Dental Journal, 2018)
It is of utmost importance that the clinician be familiar with the variations in root canal anatomy and the characteristics features in various racial groups, since such knowledge can aid location and negotiation of canals as well as their subsequent management. The aim of the present study is to investigate the incidence of three roots and four root canals in the mandibular first molar in Iraqi population. A total of 327 endodontically treated mandibular first molars were investigated in this study. Radiographs of working length determination and canal obturation at different angles of each tooth were mounted, projected and evaluated. The clinical records were reviewed and the findings for the number of roots and root canals were then recorded and tabulated. Roots with multiple canal systems were categorized according to whether the canals exited the root by a common apical foramen or by separated apical foramina. The results showed that 81.96% of the examined teeth had three root canals and the remaining 18.04% had four root canals. Most of the teeth ( 99.08% ) had two roots. Only three teeth ( 0.92% ) had three roots. There was no significant differences between males and females in the incidence of three roots and four root canals ( P > 0.05 ).